2000
DOI: 10.3758/bf03210735
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a levels-of-processing manipulation on false recall

Abstract: The present study attempted to determine the effect of a levels-of-processing manipulation on the incidence of false recall. In Experiment 1,participants engaged in either a vowel counting task or a concrete/abstract rating task; in Experiment 2, participants engaged in either a vowel counting task or a category sorting task. Results of both experiments demonstrated that participants who engaged in a deeper level of processing (i.e., concrete/abstract ratings or category sorting) recalled significantly more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
3
13

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 24 publications
7
42
3
13
Order By: Relevance
“…In contrast, the levels-of-processing manipulation had no effect on false memory rates regardless of age. The lack of a levels-of-processing effect on false recognition contrasts with previous research with adults (Rhodes & Anastasi, 2000;Thapar & McDermott, 2001;Toglia et al, 1999) that found that levels-ofprocessing either decreased or increased false recognition depending on whether information had been encoded in a shallow or a deep fashion, respectively. However, these contrasting findings may be due to individual differences in the susceptibility to false memories, something a between-participants design cannot control for.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, the levels-of-processing manipulation had no effect on false memory rates regardless of age. The lack of a levels-of-processing effect on false recognition contrasts with previous research with adults (Rhodes & Anastasi, 2000;Thapar & McDermott, 2001;Toglia et al, 1999) that found that levels-ofprocessing either decreased or increased false recognition depending on whether information had been encoded in a shallow or a deep fashion, respectively. However, these contrasting findings may be due to individual differences in the susceptibility to false memories, something a between-participants design cannot control for.…”
Section: Discussioncontrasting
confidence: 99%
“…Three studies have demonstrated that when information is encoded using deep processing, significant increases occur in both true and false memory rates relative to when that same information is processed in a shallow fashion. Moreover, these effects were obtained regardless of whether recall or recognition measures were used (Rhodes & Anastasi, 2000;Thapar & McDermott, 2001;Toglia et al, 1999). In contrast, two other studies found few effects of levels-of-processing on true and false memories (Read, 1996;Tussing & Greene, 1997).…”
Section: Levels-of-processingmentioning
confidence: 77%
See 1 more Smart Citation
“…The consequence of that might have been an inflation of false recollection rates, hence reduced accuracy, although we attempted to minimize the inflation of false memories by implementing a mixed list design. However, it is still possible that some inflation may have occurred as there is some evidence that levels-of-processing instructions can increase both false recall and recognition rates (e.g., Rhodes & Anastasi, 2000;Thapar & McDermott, 2001;Toglia, Neuschatz, & Goodwin, 1999). In order to extend the generalizability of our findings, in this last experiment we removed these potential confounds by conducting an intentional memory study in which participants were instructed to memorize neutral, negative, and survival-relevant information in a more traditional pure-list DRM format.…”
Section: Methodsmentioning
confidence: 99%
“…1 This is critical because the use of incidental memory tasks may have inflated false recollection rates, hence reduced accuracy. For example, some studies have shown that in incidental memory tasks, levels-of-processing instructions can increase both false recall and recognition rates (e.g., Rhodes & Anastasi, 2000;Thapar & McDermott, 2001). In order to extend the generalizability of the findings, we conducted an intentional memory study in which participants were instructed to memorize neutral and survival-relevant information.…”
mentioning
confidence: 99%